Hybridomas and monoclonal antibodies [ a video guide - Brinton, Charles C.; Wood, Sarah W. (Cold Spring Harbor Laboratory Press, 1994)
This video guide illustrates the sequence of steps required for success with the [hybridoma] technique [for generating monoclonal antibodies]. These include immunizing and bleeding mice; fusing spleen and myeloma cells; selecting with HAT and screening cultures; [and] growing hybridoma lines